Reassessing Critical Success Factors for ERP Implementation in the Digital Era - Wynn, Martin; Ilyas, Janat; Isleyen, Omer Faruk; Brüntrup, Henrik; Metin, Bilgin (Digital Technologies Research and Applications, 2024)
This paper examines the recent evolution of Enterprise Resource Planning (ERP) systems and explores the critical success factors (CSFs) for project implementation in the digital age. Adopting a qualitative inductive approach, the article first reports on CSFs evident in relevant literature drawn from the past two decades. In the second research phase, interview feedback from nine industry project managers is analysed to identify the CSFs now considered of particular relevance in the digital era. The article concludes that many of the established CSFs remain relevant, but recent research suggests the deployment of digital technologies and the availability of the cloud for ERP operation will mean that CSFs will be re-formulated in new technology and business environments. CSFs related to cloud-based vs on-premise software operation, system configuration and functionality trade-offs, and the integration of digital technologies into ERP products, are likely to emerge in the digital era. Future studies could profitably focus on these largely unresearched aspects of ERP projects, to which this article makes a small contribution that may provide a useful point of reference for subsequent studies.